Pelatihan Penerapan Kurikulum Merdeka pada Guru Sekolah Dasar di SD Negeri 007 Rimbo Panjang - Marta, Rusdial; Surya, Yenni Fitra; Sumianto, Sumianto (Dedikasi: Jurnal Pengabdian Pendidikan dan Teknologi Masyarakat, 2024)
This service is motivated by the fact that in the independent curriculum teachers are required to study handbooks published by the government in relation to mapping Learning Objective Achievement Indicators (IKTP) and the suitability between learning objectives and IKTP which are then adjusted to existing policies. But in reality, in schools teachers do not fully understand the independent curriculum because in the learning process teachers still feel confused about using the curriculum. The problem faced in this service is how to apply the independent curriculum to learning. The aim of this research is to find out the extent of elementary school teachers' understanding of implementing the independent curriculum among elementary school teachers at SD Negeri 007 Rimbo Panjang. With this training, teachers can better understand how to implement the independent curriculum in elementary schools. This service was carried out in Pekanbaru.